ANTI-CORRUPTION DISCLOSURE AND EARNINGS MANAGEMENT: A CASE IN INDONESIAN CAPITAL MARKET - Aprilia Nur Khasanah, Putri Dwi; Kusuma, Indra Wijaya (Jurnal Akuntansi dan Keuangan Indonesia, 2020)
This study investigates the relationship between anti-corruption disclosure and earnings management. Firms that disclose anti-corruption are related to the lower earnings management. The sample consists of 207 firm-year observation from 2016-2018. The data are hand-collected for the anti-corruption disclosure and the rest of the firm’s data are obtained from the Osiris database. Our result indicate a significant negative relationship between anti-corruption disclosure and earnings management. The relationship is more pronounce for the profitable and smaller firms. The high level of anti-corruption disclosure reported by the company can reduce earnings management actions in the company and show awareness, ability, skill, actualization of attitudes and behaviors with integrity in creating a business climate with integrity, fairness, and high competitiveness.